Dissecting the role of hyaluronan synthases in the tumor microenvironment. (22nd April 2019) - Passi, Alberto; Vigetti, Davide; Buraschi, Simone; Iozzo, Renato V.
Abstract : The tumor microenvironment is becoming a crucial factor in determining the aggressiveness of neoplastic cells. The glycosaminoglycan hyaluronan is one of the principal constituents of both the tumor stroma and the cancer cell surfaces, and its accumulation can dramatically influence patient survival. Hyaluronan functions are dictated by its ability to interact with several signaling receptors that often activate pro‐angiogenic and pro‐tumorigenic intracellular pathways. Although hyaluronan is a linear, non‐sulfated polysaccharide, and thus lacks the ability of the other sulfated glycosaminoglycans to bind and modulate growth factors, it compensates for this by the ability to form hyaluronan fragments characterized by a remarkable variability in length. Here, we will focus on the role of both high and low molecular weight hyaluronan in controlling the hallmarks of cancer cells, including cell proliferation, migration, metabolism, inflammation, and angiogenesis. We will critically assess the multilayered regulation of HAS2, the most critical hyaluronan synthase, and its role in cancer growth, metabolism, and therapy. Abstract : Hyaluronan synthase 2 (HAS2) is a key ubiquitous enzyme located at the plasma membrane that synthesizes hyaluronan and extrudes these long polysaccharides into the extracellular space. Here, we critically asses the role of HAS2 and hyaluronan in the tumor microenvironment and its regulation by a natural antisense transcript. We will also cover the function of hyaluronan in inflammation and angiogenesis.